In the Crosshairs: RNA Viruses OR Complement? - Kumar, Nisha Asok; Kunnakkadan, Umerali; Thomas, Sabu; Johnson, John Bernet (Frontiers in Immunology, 2020)
Complement, a part of the innate arm of the immune system, is integral to the frontline defense of the host against innumerable pathogens, which includes RNA viruses. Among the major groups of viruses, RNA viruses contribute significantly to the global mortality and morbidity index associated with viral infection. Despite multiple routes of entry adopted by these viruses, facing complement is inevitable. The initial interaction with complement and the nature of this interaction play an important role in determining host resistance versus susceptibility to the viral infection. Many RNA viruses are potent activators of complement, often resulting in virus neutralization. Yet, another facet of virus-induced activation is the exacerbation in pathogenesis contributing to the overall morbidity. The severity in disease and death associated with RNA virus infections shows a tip in the scale favoring viruses. Growing evidence suggest that like their DNA counterparts, RNA viruses have co-evolved to master ingenious strategies to remarkably restrict complement. Modulation of host genes involved in antiviral responses contributed prominently to the adoption of unique strategies to keep complement at bay, which included either down regulation of activation components (C3, C4) or up regulation of complement regulatory proteins. All this hints at a possible “hijacking” of the cross-talk mechanism of the host immune system. Enveloped RNA viruses have a selective advantage of not only modulating the host responses but also recruiting membrane-associated regulators of complement activation (RCAs). This review aims to highlight the significant progress in the understanding of RNA virus–complement interactions.